(untitled) (Revista Contexto & Educação, 2024)
This article aimed to dialogue with the knowledge and meanings created and moved by the Angola Janga Afro block during the Carnival in the capital of Minas Gerais. The intention was to reflect on the way in which these Afro-diasporic knowledge and senses, present in the revelry, operated in the claim of memory and the summoning of joy from a critical and creative stance towards the Brazilian context: devastated after the peak of lethality caused by the Covid pandemic -19 associated with the takeover of political-partisan power by the extreme right This is a qualitative study, based on a bibliographic review and participant observation, among others. The research findings point out that the knowledge and meanings created and movements in Carnival constitute educational, aesthetic and political anti-racist spaces-times from the black corporeities in festive movement.